2017
DOI: 10.1093/ageing/afx013
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and physical function in older HIV-infected adults

Abstract: HIV-infected patients aged ≥55 years have a high prevalence of frailty and a high burden of functional impairment. Optimal management of this population requires close collaboration between infectious diseases specialists and geriatricians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 22 publications
3
37
1
3
Order By: Relevance
“…An initial cross-sectional study in two university hospitals in Madrid (Spain) was performed. Our principal objective was to evaluate the prevalence of frailty in accordance with the criteria of Fried and to analyze physical function in a cohort of elderly HIV-1 + individuals and their results are published [22]. From the 117 elderlys included, blood samples of only 45 HIV-1 + individuals were available for the study of immune activation and oxidative stress.…”
Section: Study Design and Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…An initial cross-sectional study in two university hospitals in Madrid (Spain) was performed. Our principal objective was to evaluate the prevalence of frailty in accordance with the criteria of Fried and to analyze physical function in a cohort of elderly HIV-1 + individuals and their results are published [22]. From the 117 elderlys included, blood samples of only 45 HIV-1 + individuals were available for the study of immune activation and oxidative stress.…”
Section: Study Design and Patient Populationmentioning
confidence: 99%
“…Healthy adults present a 2:1 ratio of CD4/CD8, and the inversion of this index is related to signs of premature immunosenescence in HIV-1 + groups of different ages [21]. It has been previously shown that inadequate proportion of CD4/CD8 predict HIV infection-related clinical events in infected individuals [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Inaccurate measurements of muscle mass by DXA and other methods have led to inconsistent results and potentially erroneous conclusions about the importance of skeletal muscle mass in health and disease. PWH over 55 often have a higher burden of functional impairment and physical frailty, 21,67 although some have speculated that sarcopenia is not an important factor in HIV associated frailty. 68 The assessment of skeletal muscle mass using the D3Cr dilution method in prospective cohort studies in PWH may reveal sarcopenia as a powerful risk factor for low levels of PA, weakness, risk of falling and hip fracture, and disability.…”
Section: Measuring Skeletal Muscle Loss In Pawhmentioning
confidence: 99%
“…HIV infection has been postulated as a model of accelerated aging [2][3][4], due to the persistent and chronic activation of the immune system that leads to immune exhaustion and accelerated immunosenescence, even when on optimal immuno-virological control treatment. The clinical expression is an increased prevalence of aging-related non-HIVassociated comorbidities [5,6] and a rising prevalence of frailty occurring earlier than in the general population [7][8][9]. Thus, people living with HIV (PLWH) seem to be biologically older than their chronological age.…”
mentioning
confidence: 99%
“…In this one, the authors underline the core that constitutes the geriatrician's specific expertise and suggest putting it toward the service of complex older adults with HIV to bring value with the development of CGA integrated in a multidisciplinary team led by HIV specialists. As they point out, most older adults with HIV nowadays are robust and do not need a geriatrician's intervention, but one in four suffer from geriatric syndromes and, specifically, functional impairment [7,[11][12][13], and this 25% will be surely benefit from a geriatrician's evaluation through the CGA.…”
mentioning
confidence: 99%